Long Jump Ability: Analyze of Leg Explosive Power and Running Speed for Junior High School Students - Anggi Audina; Dewi Maya Sary; Awansyah Putra Karo Purba; Bebi Putra Sentosa Halawa (Inspiree)
The  purpose  of  the study. aims to determine the contribution of leg explosive power and running speed to long jump ability.